Wavenumber‐Splitting Metasurfaces Achieve Multichannel Diffusive Invisibility. Issue 10 (14th March 2018) - Xu, He‐Xiu; Zhang, Lei; Kim, Yongjune; Wang, Guang‐Ming; Zhang, Xiao‐Kuan; Sun, Yunming; Ling, Xiaohui; Liu, Haiwen; Chen, Zhining; Qiu, Cheng‐Wei
Abstract: The emerging invisibility schemes mainly adopt transformation optics, scattering cancellation, light diffusion, and metasurface‐based phase restoration techniques. However, those aforementioned invisibility achievements natively depend on the predefined curvature, polarization, frequency, and/or angle of the incident wave. Here, an invisibility strategy of using an ultrathin parabolic‐phase metasurface and its applications to achieve diffusive invisibility for dual‐polarization channels and multifrequency channels is reported. Such strategy can intrinsically split the wavenumber of the scattering wave and therein is termed as wavenumber‐splitting metasurface. For verification, two proof‐of‐concept examples are experimentally characterized. The first prototype manifests dual‐polarized near‐isotropic diffusive scattering immune from wide‐angle incidences. The second demonstration exhibits bifunctionality of combined diffusive invisibility and vortex scattering in dual‐polarization channels. In both cases, theoretical, numerical and experimental results agree well, illustrating a well‐separated triple‐band versatile scattering behavior. This approach addresses the fundamental issue of real invisibility under bistatic detection without complex optimization, thanks to the physical essence of numerous splitting wave vectors. Such strategy opens an upstream way to realize invisibility as well as holding the potentials for downstream applications such as stealth and camouflaging devices. Abstract : An invisibility strategy of wavenumber‐splitting metasurfaces is reported, which can achieve diffusive invisibility for dual‐polarization channels and multifrequency channels in wide‐angle incidences. Such strategy circumvents the drawbacks of emerging invisibility schemes such as transformation optics, scattering cancellation, light diffusion, and metasurface‐based phase restoration techniques, which are dependent on the predefined curvature, polarization, frequency, and/or angle of the incident wave.